Broken hallelujahs : why popular music matters to those seeking God - Scharen, Christian Batalden (Grand Rapids, Mich. : Brazos Press, 2011)
"In Broken Hallelujahs, Christian Scharen offers a fresh theological perspective on engaging faith and culture through a wide range of popular music, including the blues, hip-hop, and rock. He begins by showing the limits of approaches to culture that draw strict boundaries between saint and sinner, church and world -- approaches that may miss the creative ways God is active and at work in the world. Scharen then articulates a theology of culture that calls readers to trust God's redeeming presence in the midst of a broken creation. Through his examination of artists such as Arcade Fire, Kanye West, Leonard Cohen, and Billie Holiday, he provides a compelling theology of culture in conversation with C.S. Lewis that can look suffering and brokenness in the face because it knows of a love deeper than hate, a hope stronger than despair. Written engagingly yet with theological depth, this book will resonate with readers interested in the interface between pop culture, music, and theology, as well as with pastors and youth ministers"--Publisher description.
The seductiveness of certainty -- The holy and the broken hallelujah -- Why God loves the blues -- Cries -- Grace and karma -- Surrender to the music -- Practicing surrender.
Includes bibliographical references (pages 157-173) and indexes.
Keywords: Christianity and culture; Popular culture -- Religious aspects -- Christianity; Popular music -- Religious aspects -- Christianity